Haptic Interaction Perception, Devices and Algorithms - Kajimoto, Hiroyuki; Lee, Dongjun; Kim, Sang-Youn.; Konyo, Masashi; Kyung, Ki-Uk.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book constitutes the proceedings of the third international conference AsiaHaptics 2018, held in Songdo, Korea. It presents the state-of-the-art of the diverse haptics (touch)-related research, including perception and illusion, development of haptics devices, and applications to a wide variety of fields such as education, medicine, telecommunication, navigation and entertainment. This book is a valuable resource not only for active haptics researchers, but also for general readers wishing to understand the status quo in this interdisciplinary area of science and technology.
Perception and psychophysics of haptics -- Tactile devices for skin sensation such as vibration, pressure and temperature, and their rendering methods -- Force feedback devices and rendering methods -- Sensors such as pressure distribution sensor and force sensor -- Medical application including surgery simulation and rehabilitation -- Application of haptics to VR, telepresence and multimedia, all exploring new application area of haptics.
Keywords: Control engineering; Robotics; Automation; User interfaces (Computer systems).; Human-computer interaction; Biomedical engineering; Psychology, Experimental; Surgery; Clinical psychology; Rehabilitation; Mentally ill -- Rehabilitation; Control, Robotics, Automation; User Interfaces and Human Computer Interaction; Biomedical Engineering and Bioengineering; Experimental Psychology; Surgery; Rehabilitation Psychology